Pengaruh Customer Experience Terhadap Kepuasan Pelanggan Miniso (Survei pada Followers Instagram @minisoindo) - Salwa Rizka Rabadi; Daniel Handoko (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
Customer Experience is one of the strategies that businesses can use to attract potential customers and ensure customer satisfaction. Therefore, the one objective of this research is to examine the impact tof customer experience on Miniso’s customer experience theory, encompassing sense, feel, think, act, and relate, as well as customer satisfaction theory, which includes expectation alignment, revisit intention, and willingness to recommend products. The study adopts a quantitative approach using a survey method. Data was collected by distributing questionnaires to 86 respondents from the Instagram account @minisoindo followers. Probability sampling with simple random sampling was used for sample selection. The findings indicate that respondents agreed with the statements regarding Miniso’s customer experience. Similarly, for customer satisfaction, respondents also agrees with all statements in variable (Y) of the questionnaire. The study reveals a strong positive correlation (0.793) between customer experience and customer satisfaction, with customer experience accounting for 63% of the influence on customer satisfaction while the remaining 37% is attributed to other factors.